Evaluasi Tata Letak dan Optimalisasi Biaya Material Handling dengan Menggunakan Metode Craft: Studi Kasus: Rumah Kopi Banjarsengon - Azmilatun, Ika; Adzkia, Ryanzahra Nasywa Fatiha; Baladraf, Thabed Tholib (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Production facility layout design is an important part that must be considered in an industry. Banjarsengon coffee house is one of the coffee suppliers in Jember with product types such as robusta and arabica coffee from the Argopuro mountains. The purpose of the research is to reduce material handling costs generated by the industry in order to produce the most optimal costs, and design a proposed layout as an alternative to help reduce material handling costs. This industry processes its products from upstream to downstream so that it has 2 production sites, namely the production house and Cafe Rumah Kopi Banjarsengon. The research was conducted with an interview approach to key informants and continued by calculating material handling costs and the Craft method. The results showed that the initial layout of Banjarsengon Coffee House resulted in material handling costs of Rp. 534,437 and after iteration through the Craft Method, an alternative layout was obtained that resulted in more efficient material handling costs of Rp. 464,302. This shows that there is a material handling cost savings of 13.1% or Rp. 70,135.